Comunicação do diagnóstico de HIV: tradução do conhecimento e avaliação do conteúdo de um guia para profissionais que atendem crianças - Zanon, Bruna Pase (2020)
The communication of the diagnosis of HIV infection should be initiated in childhood with the follow-up of a multidisciplinary team in a health service. However, there is no theoretical and practical support for monitoring the communication of HIV diagnosis for children. The objectives are: to identify the scientific evidence of the elements of bad news communication in pediatrics; build the content of the communication follow-up guide for the diagnosis of HIV infection in childhood; evaluate the content of the communication follow-up guide for the diagnosis of HIV infection in childhood. This was a participatory research, based on the theoretical model of Knowledge Translation into Action, carried out in two stages. In the first, the cycle of creation of the theoretical model involving knowledge research, 2nd generation knowledge and knowledge products/tools were applied, originating the content of the technology entitled Communication of HIV diagnosis in childhood: guide for professionals who care for children. The content of the technology was created from the development of review studies, from which evidence was extracted according to the elements of communication. In the second stage, participants were selected using Fehring criteria and a committee of expert judges was set up to develop the evaluation through an online platform in the first half of 2020. The Content Validity Index (CVI) was applied and the minimum index of 0.80 was established. The ethical aspects were respected according to resolution 466/12, as well as the principles of bioethics, and the project was approved by the proposing institution. The consent of the participants was obtained through a digital ICF, also on the online platform. Judges from Brazilian states participated, composing a total of 26 judges. The technology was evaluated with global CVI of 0.94. The judges’ suggestions were met according to the technology’s objective. The content of this guide might support the care practice of professionals who care for children living with HIV, and can be incorporated by health services. From the evaluation of the content of the guide, this content is expected to base and qualify the other steps, with layout evaluation and application with the target audience. At the end of the creation of the guide, it is possible that professionals can follow the communication of HIV diagnosis to the child, supported by national and international evidence and the evaluation of renowned judges. Moreover, nursing is strengthened as a science, producing technological innovation, involving itself in monitoring the communication of HIV diagnosis to the child.